SOCIAL MECHANISMS OF COMMUNITY INFLUENCE ON THE DEVELOPMENT OF LEADERSHIP QUALITIES OF ADOLESCENTS - Mambetyarov Sharyar (Scholar Express Journal, 2024)
This article provides information on some trends in modern society that allow a new way of looking at long-term problems, showing initiative, mobility, competition - the most important human qualities, as well as some trends in teaching the formation of social mechanisms of social impact of likeminded people.
Keywords: The phenomenon of like-minded people; like-minded person; experimental; small group